Sequences and proteins that influence mRNA processing in Trypanosoma brucei: evolutionary conservation of SR-domain and PTB protein functions - Waithaka, Albina; Maiakovska, Olena; Grimm, Dirk; Melo do Nascimento, Larissa; Clayton, Christine (PLoS neglected tropical diseases, 2022)
Background Spliced leader trans splicing is the addition of a short, capped sequence to the 5’ end of mRNAs. It is widespread in eukaryotic evolution, but factors that influence trans splicing acceptor site choice have been little investigated. In Kinetoplastids, all protein-coding mRNAs are 5’ trans spliced. A polypyrimidine tract is usually found upstream of the AG splice acceptor, but there is no branch point consensus; moreover, splicing dictates polyadenylation of the preceding mRNA, which is a validated drug target. Methodology and principal findings We here describe a trans splicing reporter system that can be used for studies and screens concerning the roles of sequences and proteins in processing site choice and efficiency. Splicing was poor with poly(U) tracts less than 9 nt long, and was influenced by an intergenic region secondary structure. A screen for signals resulted in selection of sequences that were on average 45% U and 35% C. Tethering of either the splicing factor SF1, or the cleavage and polyadenylation factor CPSF3 within the intron stimulated processing in the correct positions, while tethering of two possible homologues of Opisthokont PTB inhibited processing. In contrast, tethering of SR-domain proteins RBSR1, RBSR2, or TSR1 or its interaction partner TSR1IP, promoted use of alternative signals upstream of the tethering sites. RBSR1 interacts predominantly with proteins implicated in splicing, whereas the interactome of RBSR2 is more diverse. Conclusions Our selectable constructs are suitable for screens of both sequences, and proteins that affect mRNA processing in T. brucei. Our results suggest that the functions of PTB and SR-domain proteins in splice site definition may already have been present in the last eukaryotic common ancestor.